Ancient Egyptian furniture : Volume III: Ramesside furniture - Killen, Geoffrey (Oxbow Books, 2017)
List of Figures; List of Plates; Acknowledgements; Abbreviations and Sigla; Chapter 1. Deir el-Medina -- A Community of Entrepreneurs?; Chapter 2. An Analysis of Ramesside Furniture Used in Gurob and Memphis; Chapter 3. Ramesside Furniture Forms; Chapter 4. Royal and Temple Furniture; Notes; Appendix A; Appendix B; Appendix C; Appendix D; Catalogue of Museum Collections; Plates; Bibliography.